Laikcar Sayyid Muḥammad Maḥmūd ... : dar bāb ishāʻat va maujūdah ḥālat aʻlā taʻalīm angrezī kī Musalmānon men baʻahd-i Angrezī sau (100) baras ke guzashtah zamānah men yaʻnī min ibtidāʼī 1793 lag̲h̲āyat 1893 jo unhon ne ijlās hashtam Muḥammadan Ejūkeshnal Kānfarans munʻaqidah 28 Disambar 1893 men bamuqām ʻAlīgaṛh diyā . - Mahmood, Syed (Mat̤baʻ Mufīd-i ʻām, 1894)
Text of a lecture, delivered by a noted attorney and litterateur of South Asia, Sayyid Muhammad Mahmud, barristar at law, on the status of Muslims in the field of education in India during the 100 years [1793 to 1893], at the 8th Muhammadan Educational Conference, held at Aligarh (India), on December 28, 1893.